Innovative approaches to nail and skin health in professional manicure - Kolomoiets, Olena (Global Prosperity, 2025)
Abstract. The article is dedicated to the analysis and systematization of innovative approaches to nail and skin care in the context of professional manicure, with a focus on the integration of scientific, technological, and sustainable solutions in modern beauty practices The purpose of this article is to analyze and systematize innovative approaches to nail and skin health within the context of professional manicure, emphasizing the integration of scientific, technological, and sustainable principles in modern beauty practices. During the scientific research, general scientific methods of cognition were used: analysis, synthesis, comparison, generalization, systematization, forecasting, and modeling. The results of the study show that the modern manicure industry is undergoing a deep transformation due to the implementation of innovations focused on safety, personalization, and environmental responsibility. Emphasis is placed on the changing approach to nail care – from decorative treatment to preventive and therapeutic procedures using “breathable”, hypoallergenic, multifunctional, and probiotic formulas. The study examines coating technologies, among which gel polishes, dip systems, and nanocosmetics stand out, providing deep penetration of active components and increased formula stability. It is shown that the latest methods are based on the principles of functional dermatology and microbiome support. The paper also analyzes the use of digital and artificial intelligence solutions in the field of nail care. In particular, it examines the implementation of smart gadgets for diagnosing nail condition, 3D printing, mobile applications for virtual design, and platforms with virtual color try-on features. It is demonstrated that such solutions contribute to high-precision personalization of services and increased procedural effectiveness. Special attention is given to the concept of the Internet-of-Mirrors – sensor mirrors capable of analyzing nail and skin parameters, integrating with recommendation service systems. It is shown that a key development vector of the industry is a sustainable approach to production – active implementation of biodegradable polymers, rejection of toxic components, the use of eco-packaging, and the development of “5-Free” and “10-Free” initiatives. The update of professional training for specialists has been studied, including education in sustainable development, digital technologies, and wellness manicure. Market analytical forecasts have been analyzed, indicating the stable growth of the industry due to the combination of aesthetics, health, and innovation. A conclusion is made about the gradual intellectualization of nail services, including robotics, automation, and the implementation of cybersecurity protocols. The practical significance of the study lies in the formation of a scientifically grounded basis for the modernization of professional nail care practices, taking into account technological, medical, and environmental criteria.